Hybrid Photocatalyst for Corrosion Reducing and Sustainable Concrete Construction - Nath, Ranjit Kumar; M .Zain, M. F.; Alam, Md. Rabiul; Kadhum, Abdul Amir H.; Kaish, A.B.M.A. (International Journal of Sustainable Construction Engineering and Technology, 2012)
Corrosion is the main problem in Reinforced concrete (RC). RC usually absorbs carbon dioxide from surrounding environment in operational period. This carbon dioxide reacts with the calcium oxide, which is already present in RC and forms a calcium carbonate an acidic compound that enhances corrosion on the surface of the reinforcement. Addition of photo catalytic materials to the RC structure during its construction phase could reduce the corrosion problem of RC materials. This material hinders calcium oxide to form acidic compound and creates a complex compound. In combination with light, this complex compound is oxidized, and residual compound will exist in or surface of RC material. In this study it is aimed to find out the proper photo catalytic material adjustable with RC material for reducing corrosion problem and enhancing oxidization process of volatile organic compounds.